Gender differences in acute ischemic stroke - Förster, Alex; Gass, Achim; Kern, Rolf; Wolf, Marc; Ottomeyer, Caroline; Zohsel, Katrin; Hennerici, Michael G.; Szabo, Kristina (Stroke, 2009)
Background and Purpose: Differences between women and men in relation to stroke are increasingly being recognized.Methods— From July 2004 until June 2007, 237 acute ischemic stroke (AIS) patients were treated with recombinant tissue plasminogen activator (rtPA) within 3 hours after onset of symptoms in our stroke unit. Baseline characteristics, etiology, CT/MRI stroke patterns, clinical outcome, and complications of women were compared to those of men.Results— Of 237 AIS patients (mean age 70.7 years), 111 (46.8%) were women and 126 (53.2%) were men. Women were older (P=0.001), but history of hyperlipidemia (P=0.03), smoking (P=0.03), and coronary heart disease (P<0.001) was less frequent than in men. Internal carotid artery disease occurred more often in men (P=0.02), whereas atrial fibrillation was observed more often in women (P=0.002). In men borderzone/small embolic and lacunar stroke was found more frequently (39.7 versus 27.2%), whereas women showed a higher percentage of large territorial stroke (72.8 versus 60.3%, P=0.09). Baseline National Institute of Health Stroke Scale scores (12.5 versus 11.3), NIHSS score at discharge (11.0 versus 9.5), 3-month-outcome modified Rankin Scale score, thrombolysis-related (17.1% versus 13.5%) or independent complications (32.4% versus 30.2%), and mortality after 3 months (13.5% versus 9.5%) were similar.Conclusion— Differences of stroke lesion patterns in genders are paralleled by differences in etiology and risk factor profiles (women, cardioembolism; men, large and small vessel disease). Baseline characteristics, rates of rtPA-related and independent complications, as well as clinical outcomes were not different between women and men with AIS.
Gesehen am 17.03.2021